An Efficient, Facile Synthesis of Etoricoxib Substantially Free from Impurities: Isolation, Characterization and Synthesis of Novel Impurity. Issue 30 (23rd October 2017) - Awasthi, Arun Kumar; Kumar, Brijesh; Aga, Mushtaq A.; Basha, Shaik Thaslim; Reddy, Cirandur Suresh; Kumar, Pramod
Abstract: A copper mediated efficient, facile synthesis of Etoricoxib from commercial available keto sulfone and vinamidinium salt was developed. This protocol with mild reaction conditions offered the product with >80% overall yield and remarkable quality. During process development an unknown impurity was observed, isolated, characterized (by NMR, mass and IR spectroscopy) and was identified as Pyrrole derivative. Abstract : A copper mediated efficient, facile synthesis of Etoricoxib from commercial available keto sulfone and vinamidinium salt was developed. This protocol with mild reaction conditions offered the product with >80% overall yield and remarkable quality. During process development an unknown impurity was observed, isolated, characterized (by NMR, mass and IR spectroscopy) and was identified as Pyrrole derivative.